Do e-athletes move? A study on physical activity level and body composition in elite e-sports - Akan Bayrakdar; Yağmur Yıldız; Işık Bayraktar (Physical Education of Students)
Background and Study Aim. The aim of this study is to determine the effect of e-sports on physical activity level and body composition.